PENGARUH KEMUDAHAN AKSES DAN PERILAKU KONSUMTIF TERHADAP PENGGUNAAN SHOPEEPAY SEBAGAI ALAT PEMBAYARAN DIGITAL PADA MAHASISWA S-1 DAN D-4 FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS NEGERI JAKARTA - Ditto Habib Yudha Mahardhika; Ivan Fadhillah Syakieb, Muhammad Rizal Romdoni, Ravi Raditya Kurniadi (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to evaluate the impact of Ease of Access and Consumptive Behavior on the use of ShopeePay as a digital payment method. The approach used is a quantitative method, with data collected through questionnaires filled out by 58 active undergraduate and diploma students from the Faculty of Economics and Business at Universitas Negeri Jakarta, who are ShopeePay users. Data analysis was conducted using multiple linear regression with the assistance of SPSS and Stata software. The research findings indicate that both independent variables, Ease of Access and Consumptive Behavior, have a positive and significant influence, both partially and simultaneously, on the use of ShopeePay as a digital payment tool.